Participation of Argawana Citra Art Center Community in Tourism Activities at the Betawi Setu Babakan Cultural Village - Gagih Pradini; Tonny Hendratoni; Azril Azahari; Tutut Herawan (CV ODIS, 2023)
Tourism is one of the activities that can stimulate the economic development of a country. Indonesia, rich in natural beauty and culture, has great potential for tourism development. Currently, the community-based tourism development model is widely implemented in the form of tourism village development. Tourism village development is very implemented for tourism development in Indonesia because of its rich local and natural wisdom. Betawi Setu Babakan Cultural Village is one of the results of community participation-based tourism development. Community participation activities that are running well have improved the economy and creative activities that involve the community in it. One community that plays a role in tourism activities in the Betawi Setu Babakan Cultural Village is the Argawana Citra Art Center. This research will use descriptive quantitative research methods in the process. This research intends to identify and analyse the role and obstacles of the community, namely the Agrawana Image Art Studio, in tourism activities in the Betawi Setu Babakan Cultural Village. This study found that Argawana Citra Art Center has preserved and maintained Betawi culture and introduced Betawi culture through ondel-ondel making workshops and other craft arts.